1959
DOI: 10.1071/bi9590388
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Lateral Root Induction by Root Initials in Isolated Flax Roots

Abstract: When ,B-indolylacetic acid (IAA) (10-5M) is added to isolated flax roots, lateral roots are induced to form adventitiously. If some lateral root initials are already present when IAA is added, newly induced primordia form preferentially immediately adjacent to them. It is suggested that a chemical stimulus, a kinin, originating from the existing root meristems interacts with IAA to induce further cell division in the pericycle. It is proposed that kinin formation may be a normal accompaniment of cell division.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

1961
1961
2000
2000

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…An alternative option is that for operation of the second growth control point no founder cell formation is needed. Experiments showing that practically all pericycle cells in the xylem radii participated in LRP formation (Goldacre, 1959;Blakely et al, 1982;Laskowski et al, 1995) indicate such a possibility. In contrast with other tissues in the root differentiation zone, pericycle cells do not endoreduplicate (Blakely and Evans, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative option is that for operation of the second growth control point no founder cell formation is needed. Experiments showing that practically all pericycle cells in the xylem radii participated in LRP formation (Goldacre, 1959;Blakely et al, 1982;Laskowski et al, 1995) indicate such a possibility. In contrast with other tissues in the root differentiation zone, pericycle cells do not endoreduplicate (Blakely and Evans, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Goldacre (8) obtained evidence for the production of a cytokinin-like substance by the dividing cells of unemerged root initials in isolated flax roots, and proposed that cytokinin production may be a normal accompaniment of cell division. Furthermore, Torrey (35) suggested that the quiescent zone may be the site of highest cytokinin concentration in the root SIN ROOTS 159 tip.…”
Section: Discussionmentioning
confidence: 99%
“…Pecket (1957aPecket ( , 1957b has presented evidence of a factor other than auxin involved in lateral root formation in peas. Goldacre (1959) suggested that root primordia might produce a cytokinin, which would interact with auxin to induce cell division in the pericycle, and Torrey (1962) found that kinetin stimulated branching in isolated pea roots. In cultured radish roots the production of an endogenous cytokinin by primordia might be expected to stimulate the formation of a multiseriate pericyclic zone, as applied BA does.…”
Section: Department Of Agronomy and Range Science University Of Calimentioning
confidence: 99%